Roxatidine- and Cimetidine-Induced Angiogenesis Inhibition Suppresses Growth of Colon Cancer Implants in Syngeneic Mice - Kazuyoshi Tomita; Kazuki Izumi; Susumu Okabe (Elsevier, 2003)
ABSTRACT: Cimetidine is known to suppress the growth of several tumors, including gastrointestinal cancer, in humans and animals. Nonetheless, whether other histamine H2-receptor antagonists exert such tumor suppressive effects remains unclear. The effect of roxatidine acetate hydrochloride (roxatidine), an H2-receptor antagonist, on the growth of colon cancer implanted in mice was examined and compared with that of cimetidine. Drugs were orally delivered for 26 - 29 days beginning before or after implantation of syngeneic colon cancer (Colon 38) in C57BL/6 mice. Tumor volume was determined throughout and histochemical analysis was also performed. Tumor tissue and serum vascular endothelial growth factor (VEGF) levels were measured. In vitro cell growth was assessed by the MTT assay. Both roxatidine and cimetidine significantly suppressed the growth of Colon 38 tumor implants. Histologic analysis revealed that such antagonists markedly increased necrotic areas and decreased the density of microvessels in tumor tissue. Both H2-receptor antagonists suppressed VEGF levels in tumor tissue and significantly decreased serum VEGF levels in Colon 38-bearing mice. Such drugs, however, failed to suppress in vitro growth of the cell line. In conclusion, both roxatidine and cimetidine were found to exert suppressive effects on the growth of colon cancer implants in mice by inhibiting angiogenesis via reducing VEGF expression.